PERENCANAAN GEDUNG SENI LUKIS DI KOTA SAMARINDA - Setiawan, Arta Iman; Milasari, Lisa Astria; Riza, Ahmad (LPPM Universitas 17 Agustus 1945 Samarinda, 2021)
Painting is one of two dimensions of art that is rarely found by the public. Samarinda has a variety of painting communities, including mural painting, graffiti painting and typographic painting. The background of this writing is due to the community's need to be able to know and learn about mural painting, graffiti and typography as well as providing facilities for the painting community in Samarinda City. The formulation of the problem in this study is how to plan the Painting Building in Samarinda City with a hybrid architecture approach to the building. So that the purpose of this research is to plan the Painting Building in Samarinda City which has complete painting facilities with a Hybrid Architecture approach to the building. Making this research using data collection methods with field observations and literature studies that support the theory of problem solving. The method used in this research is descriptive research methods and analytical research methods, descriptive research methods are primary data and secondary data, for the analysis method is a space program analysis, site analysis and analysis with a hybrid architecture approach with 3 stages namely, ectetic, manipulation, and merging. From the results of the discussion in the form of a total amount of space equal to KDB of 4,896 m2 and KDH of 11,424 m2, the land requirement used is 16,320 m2, for selected locations located on Jalan Kadrie Oening kec. Samarinda Ulu with a score of 14. In the analysis and concept emphasis is prioritized on building facades with basic shapes of circles and squares.Keywords: painting, building, hybrid